Strategic Management of MSME Individual Company Program by the Ministry of Law and Human Rights - Burhan, Muhammad Rahmatul; Costiana, Sterinalita (JURISMA : Jurnal Riset Bisnis & Manajemen, 2025)
Indonesia has the largest number of MSMEs in Southeast Asia. Very few of them are legal. The government introduced the Individual Company (Perusahaan Perseorangan) program to address this issue. The highlighted issue is the socialization activities by the Ministry of Law and Human Rights of the Republic of Indonesia. This study aims to assess whether the socialization strategy conducted is well received by MSMEs, as well as its sustainability strategies, and whether this socialization strategy can move MSMEs toward the objectives set by the organization. This study was conducted in the West Nusa Tenggara Province (Nusa Tenggara Timur/NTB) with phenomenological principles, using Interpretative Phenomenological Analysis (IPA) as data analysis by combining two measurements, namely RMT and EPIC Model, which have never been done before in other studies. Based on Relationship Management Theory and the EPIC Model, this study shows that the Ministry of Law and Human Rights applies an attractive and persuasive strategy so that MSMEs understand the objectives it conveys through the socialization of Individual Companies. An ongoing strategy is also carried out to maintain relationships with MSMEs.  Keywords: MSMEs; Management; Strategic Management; Individual Company; Phenomenology